Effect of stress on study skills self-efficacy in Nursing students: the chain mediating role of general self-efficacy and self-directed learning - Xiaoyun Zhang; Lei-lei Guo; Ying Wang; Yuqing Li; Jiaofeng Gui; Xue Yang; Yujin Mei; Haiyang Liu; Jin-long Li; Yunxiao Lei; Xiaoping Li; Lu Sun; et al. (BMC, 2024)
Abstract Background The purpose of the study is to explore the current level of nursing students' study skills self-efficacy, and whether general self-efficacy and self-directed learning ability mediate the relationship between perceived stress (including positive stress and negative stress) and study skills self-efficacy. Methods The survey was conducted among 1,289 nursing students including 795 students from Jinzhou Medical University and 494 students from Dalian University. Participants completed a self-designed questionnaire, which included the Study Skills Self-Efficacy Scale, Perceived Stress Scale, General Self-Efficacy Scale, Self-Directed Learning Instrument, gender, age, academic year, and other demographic characteristics. Descriptive analysis, independent-samples t-test, one-way analysis of variance, Pearson correlation analyses, and the bootstrap method were used for data analysis. Results Positive stress significantly positively predicted students' study skills self-efficacy, with an effect size of 0.686. Moreover, general self-efficacy and self-directed learning mediate the relationship between positive stress and study skills self-efficacy in nursing students, with effect sizes of 0.235 and 0.245, respectively. The direct effect of negative pressure on students' study skills self-efficacy is not statistically significant, but it has a significant negative predictive effect on study skills self-efficacy under the mediation of general self-efficacy and self-directed learning, with effect sizes of -0.337 and -0.238, respectively. Conclusion This study explains how stress affects students' study skills self-efficacy, and the results have certain enlightenment significance for improving the stress management ability and study skills self-efficacy of college students in the future.